Customer relationship management: Concept and importance for banking sector - Marko Laketa; Dusica Sanader; Luka Laketa; Zvonimir Misic (UTMS Journal of Economics, 2015)
Customer Relationship Management concept is tendency of banking sector to establish and maintain long-term relationships with customers in order to provide value for customers and banks. This concept allows bank to identify, segment, communicate and build long-term relationships with customers on individual basis. In today's business environment, banks have aim to identify customers and to adjust offer to meet customer's needs, in order to maximize profits. Using modern technologies, Customer Relationship Management is becoming a method to maintain existing structure and development of high quality customer base. It involves development of marketing strategy through a better understanding of the entire customer base, understanding needs and attitudes of customers, as well as more efficient consideration of profitability and added value that each customer have for the bank. The aim of research, presented in this paper, is to assess to benefits of introducing Customer Relationship Management concept in banking sector, by defining strategies, adjustment of organizational structure, culture and internal processes with help of modern technology. The paper presents methods of measuring success of Customer Relationship Management concept and problems which banks have when implementing a new business philosophy.
Keywords: M31; E44; 330; CRM concept; CRM strategy; processes; information technology; communication channels